The detection of infectious bronchitis viral antigen by means of immunohistochemical technique in broiler chicken infected with I-269 IB isolate or injected with H-120 live vaccine - Damayanti, Rini; ., Darminto (Indonesian Animal Sciences Society, 2001)
A study was carried out to detect the antigen of infectious bronchitis vius (IBV) in broiler chicken by means of immunohistochemical technique. A total of 150 - fourteen days old broiler chicken were divided into three groups i.e. 50 chicken were infected with an IB isolate of I-269, 50 chicken were injected with H-120 life vaccine, and 50 chicken served as un-treated control. Clinical signs and gross pathological changes were observed. Each of five chicken of each group were necropsied at 1, 2, 3, 4, 7, 10, 14, 21, 28, and 35 day(s) post infection/vaccination. The antigen could be detected at one day through 35 days post vaccination/infection. In the vaccinated group, histopathological lesions and the detected antigen were minimal. In contrast, the infected chicken showed varied histolopathological lesion in accordance with the numerous antigens. The antigen were observed in the lymphocytes/macrophages in the trachea, lungs and kidney, and in the epithelium of trachea, alveoli, broncheolus and tubular sitoplasm of the kidney of both vaccinated and infected groups. In the infected group, antigen was also detected in the lymphocytes and macrophages of the affected organs. Â Key words: Infectious bronchitis, broiler chicken, I-269 IB isolate, immunohistochemistry